The disassembly of the neuromuscular synapse in high-fat diet-induced obese male mice - Isabel Martinez-Pena y Valenzuela; Mohammed Akaaboune (Elsevier, 2020)
Objective: A sustained high fat diet in mice mimics many features of human obesity. We used male and female Non-Swiss albino mice to investigate the impact of short and long-term high-fat diet-(HFD)-induced obesity on the peripheral neuromuscular junction (NMJ) and whether obesity-related synaptic structural alterations were reversible after switching obese mice from HFD to a standard fat diet (SD). Methods: HFD-induced obese and age-matched control mice fed SD were used. We carried out in vivo time lapse imaging to monitor changes of synapses over time, quantitative fluorescence imaging to study the regulation of acetylcholine receptor number and density at neuromuscular junctions, and high resolution confocal microscope to study structural alterations in both the pre- and postsynaptic apparatus. Results: Time-lapse imaging in vivo over a 9 month period revealed that NMJs of HFD obese male mice display a variety of obesity-related structural alterations, including the disappearance of large synaptic areas, significant reduction in the density/number of nicotinic acetylcholine receptor (AChRs), abnormal distribution of AChRs, high turnover rate of AChRs, retraction of axons from lost postsynaptic sites, and partially denervated synapses. The severity of these synaptic alterations is associated with the duration of obesity. However, no substantial alterations were observed at NMJs of age-matched HFD obese female mice or male mice fed with a standard or low fat diet. Intriguingly, when obese male mice were switched from HFD to a standard diet, receptor density and the abnormal pattern of AChR distribution were completely reversed to normal, whereas lost synaptic structures were not restored. Conclusions: These results show that the obese male mice are more vulnerable than female mice to the impacts of long-term HFD on the NMJ damage and provide evidence that diet restriction can partially reverse obesity-related synaptic changes.